A variabilidade hidrológica e sua influência sobre as formas iniciais de peixes em um rio situado numa bacia Neotropical. - Kipper, Darlon (2015)
Among the different species of fish, the life cycle is synchronized to avoid or exploit flows with magnitudes variables. For example, the natural frequency of high or low flow trigger the different stages of the life cycle, such as spawning, incubation of eggs, the initial development and the lateral migration in the flood plain. However, the timing of each of these characteristics with the attributes of floods, strategies presented depends on the species, being complex events and their interdependence has not yet fully understood. In this study it was found over five reproductive periods, the effect of flow regime and its components on the dynamics of ichthyoplankton in this Ivinheima river and two ponds connected to this system. The variation in the abundance of fish eggs and larvae over a reproductive period and was verified that there were changes in the composition of the assemblage and its relationship with environmental variables were assessed. For the five reproductive periods, the attributes of the flood pulse were calculated by PULSO software and soon after were summarized by a PCA. Possible differences in the density of eggs and larvae between reproductive periods, and in only one period were tested with Permutational Multivariate Analysis of Variance. For the similarity of patterns in the assembly of larvae were used Non-metric Multidimensional Scaling. To test the relationship of the biota of the attributes with the hydrological variability and environmental variables were used Spearman correlations. Higher densities of eggs were recorded in Ivinheima river in flood periods. The density of larvae was similar in the environments, and the Finado Raimundo lagoon had greater abundance in the river there was a predominance of migratory species, as in the lagoons was the domain of sedentary species. The assemblage of larvae presented is structured in the months in which they were checked the flood pulses, migratory species organized in the early months and in the later months predominant species with different reproductive strategies. It can also be noted that dry and intermediate years have importance for the reproduction of species, mainly sedentary. In the reproductive period, higher densities of larvae occur in the months of highest precipitation, tests showed significant differences between the months and revealed that migratory species were related to the months of highest precipitation. The densities of eggs and larvae, as well as some migratory species were positively correlated with rainfall, while the temperature was negatively correlated with the migratory. We conclude that the most extensive floods favored fish reproduction, ascertained by the greatest abundance of eggs and larvae in these periods, as well as to favor migratory species and also caused the increase of wealth in some habitats. For the reproductive phase is concluded that the seasonality of reproduction of the species (especially migratory) presents synchrony with the rainy periods. On the other hand in the months with low rainfall occurs playing some species with large reproductive plasticity.